1997
DOI: 10.1159/000310780
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Pharmacology and molecular Biology of the Trabecular Meshwork Inducible glucocorticoid Response Gene Product

Abstract: Studies of the effects of glucocorticoid (GC) and oxidative stress stimuli in differentiated cultures of human trabecular meshwork (HTM) cells have provided the rationale for our studies of a major new gene termed TIGR (trabecular meshwork inducible GC response). The TIGR clone was isolated by differential library screening using selection criteria based on the induction pattern of a new protein/glycoprotein found in HTM cultures after prolonged but not brief exposure to GCs. This GC induction patter matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
209
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(229 citation statements)
references
References 4 publications
(6 reference statements)
11
209
1
2
Order By: Relevance
“…The 66-kDa form of TIGR might be retained in the meshwork due to predicted interactions with other extracellular matrix molecules. An in vivo role for TIGR (and its potential effect in obstructing outflow) is reinforced by recent findings of increased TIGR gene products in DEX-treated organ culture and glaucoma eyes (43). DISCUSSION In this paper, we have shown that the induction of the TIGR gene expression in TM cells by prolonged DEX treatment results in high levels of new extracellular proteins.…”
Section: Candidate Clone Selection and Induction Characteristics-mentioning
confidence: 52%
See 1 more Smart Citation
“…The 66-kDa form of TIGR might be retained in the meshwork due to predicted interactions with other extracellular matrix molecules. An in vivo role for TIGR (and its potential effect in obstructing outflow) is reinforced by recent findings of increased TIGR gene products in DEX-treated organ culture and glaucoma eyes (43). DISCUSSION In this paper, we have shown that the induction of the TIGR gene expression in TM cells by prolonged DEX treatment results in high levels of new extracellular proteins.…”
Section: Candidate Clone Selection and Induction Characteristics-mentioning
confidence: 52%
“…It also has a consensus HA binding sequence Arg-Arg-Gly-Gln-Cys-Pro-Ser-Thre-Arg (at aa 181-189) that resembles the consensus motif B(X 7 )B, in which B is a basic aa and X is any aa (25). The cDNA also contains the GAG initiation sites Asp-Gln-Ser-Gly (at aa [42][43][44][45] and Ser-Gly-Glu-Gly (at aa 238 -241) sequences that match consensus motifs Asp-Xss-Ser-Gly and Ser-Gly-Xaa-Gly described for proteoglycans (26,27). Other important features of the molecule include clusters of two and seven leucine zippers and an olfactomedin homology domain of 178 aa at the carboxyl terminus that is considered in greater detail later.…”
Section: Candidate Clone Selection and Induction Characteristics-mentioning
confidence: 99%
“…MYOC/TIGR was originally isolated from cultured human TM cells expressing this protein in high amounts following long-term treatment with dexamethasone and, independently, from normal human retina (Fauss et al 1993;Nguyen et al 1993;Kubota et al 1997;Polansky et al 1997). In addition to TM and retina, MYOC/TIGR is expressed in other ocular tissues such as the cornea, sclera, ciliary body, iris and optic nerve head (Adam et al 1997;Ortego et al 1997;Tomarev et al 1998;Karali et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Another group consists of annexin A3, se20-4 tumor antigen, and myocilin (Table 1). Annexin is an inhibitor of phospholipase A2 (PLA-2) (Oh et al 2000); se20-4 tumor antigen is the nucleolar TGF-␤1 target protein (Ozbun et al 2001); and myocilin is a trabecular meshwork-inducible glucocorticoid response protein (Polansky et al 1997). As TGF-␤1 and glucocorticoid attenuate IL1-␤-induced PLA2 elevation (Muhl et al 1992), these three genes might be common downstream targets of TGF-␤ or glucocorticoid signaling.…”
Section: Figure 2 (Continued On Facing Page)mentioning
confidence: 99%